Validation of the arabic version of the edinburgh postnatal depression scale for screening antenatal depression in Oman - Khalood Al-abri; Hana AL Sumri; Mohammed Al-Azri; Divya Kuzhivilayil Yesodharan; Rahma Al Kindi (BMC Pregnancy and Childbirth)
Abstract Background Antenatal depression is a common mental health problem that women experience during their pregnancies. If left untreated, it can increase a woman's risk of developing postnatal depression and have adverse effects on both mothers and children. Therefore, early identification of depression requires a valid screening tool. The Edinburgh Postnatal Depression Scale (EPDS) is still the most widely recognised screening instrument used to identify symptoms of postnatal depression. Despite the existence of a general Arabic version, it may not accurately reflect the unique cultural characteristics and healthcare practices of Oman. Therefore, the validity of the EPDS for antenatal depression remains uncertain, as no studies have yet addressed its validation in this population. Aims To establish the validity of the Omani Arabic version of EPDS with an optimal cut-off value as a screening instrument to identify symptoms of depression among women attending antenatal care. Methods A thoroughly translated and modified Arabic Omani version of the EPDS was designed and validated, with the Arabic PHQ-9 being used as the gold standard. Self-questionnaires were distributed to a sample of 352 women receiving antenatal care at University Medical City Oman and five primary healthcare centres in Muscat governorate, the capital city of Oman. Receiver Operator Characteristic curve was plotted, the area under the curve was calculated, and the optimal cut-off value was identified using Youden’s index. Results The Omani version validation of the EPDS yielded an optimal cut-off score of 11/12 for antenatal depression, with sensitivity, specificity, positive and negative predictive values of 86.30%, 71.37%, 45.65%, and 94.92%, and an area under the curve of 0.85. Youden's index reached a maximum at 0.58 with a cut-off point of 11. The optimal cut-off value is 10 in the first trimester (Youden’s index 0.63) with sensitivity of 100.00% and specificity of 63.16%, 11 in the second trimester (Youden’s index 0.56) with sensitivity of 86.21% and specificity of 69.90%, and 12 in the third trimester (Youden’s index 0.60) with sensitivity of 78.57% and specificity of 80.99%. The internal consistency using Cronbach’s alpha was 0.70, indicating acceptable reliability. Conclusion The study's findings indicate that the Omani version of the EPDS as a valid instrument to screen symptoms of antenatal depression among Omani women.